(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
In the article were evaluated some parameters of the agricultural and industrial yield in canes cut in function of the time lapsed from the cut until the ground one in three sugar cane varieties in the UBPC "Realengo". The valued variables were: weigh of the shafts, Brix, Pol, Purity and potential Yield of the cane. The valued times were: 12, 24, 36 and 48 hours. The objective was to establish a program of appropriate handling of the crop that diminishes the affectations for this concept, by means of the study of the freshness of the main sugar cane varieties. These presented a considerable deterioration of the evaluated physiologic parameters, being the weight of the shafts the most affected starting from the 36 hours, elevating the value of the indicator significantly differs of weight field-batey. For effect of the time of cut the cane without being processed affected the value of the purity of all the varieties, as consequence the potential yield diminished significantly. The varieties of more affectations in the parameters of the agricultural and industrial yield caused by the time of cut were C 86 - 503 and Cp 52 - 43, those that had court preference and shot, and you achievement to minimize the time of permanency in the field after the cut, optimizing the use of the resources proposed in the planning of the crop.